2017
DOI: 10.1186/s12885-017-3132-9
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of miR-146a increases the sensitivity of non-small cell lung cancer to DDP by downregulating cyclin J

Abstract: BackgroundCisplatin (DDP)-based chemotherapy is the common first-line therapy for lung cancer. However, their efficacy is often limited by primary drug resistance and/or acquired drug resistance. The aim of this study was to investigate the function of miRNA-146a (miR-146a) in DDP-resistant non-small cell lung cancer (NSCLC), as well as the underlying mechanisms.MethodsThe effect of overexpression of miR-146a and/or knockdown of cyclin J (CCNJ) in A549/DDP and SPC-A1/DDP cells were investigated as follows. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 50 publications
(36 reference statements)
4
36
0
Order By: Relevance
“…The other miRNAs of this six miRNA panel had no significant differential changes. miR-146a-5p has been previously reported to be involved in the regulation of resensitization of cisplatin-resistant NSCLC cells (36). However, we failed to observe the impact of miR-146a-5p on the response to cisplatin through overexpression or silencing of miR-146a-5p in NSCLC cells, including PC-9, SPCA1, H1299, and H1975 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 65%
“…The other miRNAs of this six miRNA panel had no significant differential changes. miR-146a-5p has been previously reported to be involved in the regulation of resensitization of cisplatin-resistant NSCLC cells (36). However, we failed to observe the impact of miR-146a-5p on the response to cisplatin through overexpression or silencing of miR-146a-5p in NSCLC cells, including PC-9, SPCA1, H1299, and H1975 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 65%
“…The authors attributed an oncogenic role of miR‐146a to targeting of DNA damage inducible transcript 3 (CHOP), a gene whose low expression is correlated with poor prognosis. Additionally, they suggested miR‐146a can promote NSCLC resistance to cisplatin (Tan et al, ), while two other publications showed the opposite (Shi et al, ; Yuwen et al, ). Overall, the conclusions made by Tan et al are questionable because multiple articles refute numerous aspects of their experimental results.…”
Section: Role Of Mir‐146a In Specific Cancersmentioning
confidence: 99%
“…Clinically, patients with low miR‐146a expression in their lung tumors tended to have advanced stage cancer and metastases, while patients with high miR‐146a levels demonstrated longer progression‐free survival (Chen et al, ). Cell cycle progression is also slowed by miR‐146a, in part by specifically targeting cyclins D1/2 (Li et al, ) and cyclin J (Shi et al, ). These in vitro results were replicated in a xenograft mouse model, where implanted cells overexpressing miR‐146a formed smaller tumors (Li et al, ).…”
Section: Role Of Mir‐146a In Specific Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuwen et al [66] identified that serum exosomal miR-146a-5p might be a new biomarker for predicting the efficacy of DDP for NSCLC patients and real-time monitoring drug resistance. Shi et al [67] also investigated the role of miR-146a in the development of acquired drug resistance to DDP in NS-CLC cells, and found that overexpression of miR-146a significantly increased the sensitivity of NSCLC cells to DDP via blocking the cell cycle, enhancing cell apoptosis, and inhibiting cell viability and motility both in vitro and in vivo. Ma et al [68] reported that DLK1 was a potential target for miR-129-5p, and overexpression of miR-129-5p could inhibit NSCLC chemo-resistance to DDP through regulating DLK1.…”
Section: The Prognostic Value Of Mirnas In Nsclcmentioning
confidence: 99%